Morphological Identification and Evaluation of Phytochemical Content and Antioxidant Activity of Gembili Tuber (Dioscorea esculenta L.) in Malaysia - Mohammad Raiehan Prayoga; Asritanarni Munar; Razali Bin Mirad (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Gembili tuber (Dioscorea esculenta L.) is a tuberous plant known for its high nutritional value and richness in bioactive compounds. These bioactive compounds, including diosgenin, β-sitosterol, and saponins, offer various health benefits, such as antimicrobial, anticancer, and antioxidant properties, crucial in preventing degenerative diseases. This study aims to investigate the differences in phytochemical and antioxidant content of Gembili tubers from different locations. The research was conducted at the Phytochemical Laboratory, MARDI, in Selangor, Malaysia, where the total phenolic content (TPC) was analyzed using the Folin-Ciocalteu method, and the antioxidant capacity was assessed through the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay using a UV spectrophotometer (Eon Biotek) at 517 nm. The results indicated that the total phenolic content and antioxidant values of yam bean tubers from the Serdang location in Selangor were higher than those from the Port Dickson location in Negeri Sembilan, measuring 1.6940 mg GAE/100g and 0.366 mg/ml in the DPPH test, respectively. Consequently, yam tubers cultivated in Serdang, Selangor, demonstrate greater potential as a source of natural antioxidants beneficial for health than those grown in Port Dickson.